Multivariate time series online prediction based on adaptive normalized sparse kernel recursive least squares algorithm - Shuhui Zhang; Min Han; Jun Wang; Dan Wang (2017 Seventh International Conference on Information Science and Technology (ICIST), 2017)
As a kind of kernel methods, kernel recursive least squares has attracted wide attention in the research of time series online prediction. It has low computational complexity and updates in the shape of recursive increment. However, with the increase of data size, computational complexity of calculating kernel inverse matrix will raise. In addition, in the process of online prediction, it cannot accommodate dynamic environment commendably. It is difficult to meet the demand of prediction accuracy and efficiency simultaneously. Therefore, this paper presents an improved kernel recursive least squares algorithm for multivariate chaotic time series online prediction. We apply dynamic adjustment and coherence criterions to propose adaptive normalized sparse kernel recursive least squares (ANS-KRLS) method. In our method, the size of kernel matrix can be reduced, so that computational complexity drops. And ANS-KRLS has the ability to operate online and adjust weights adaptively in time-varying environments. The proposed method has been simulated on Lorenz time series and ENSO related indexes time series. Simulation results prove that ANS-KRLS performs well on prediction accuracy and efficiency.